Dual parallel process in crisis situations: motivational foundation/ el doble procesamiento paralelo en situación de crisis: fundamentación motivacional/ o dobro processamento paralelo em situação de crise: fundamentação... (2012)
The objective of this paper is to present a cognitive-behavioral model that makes it possible to explain the crisis situation (CS) in terms of intense motivational involvement, and to propose a brief motivational intervention proposal in CS. The CS requires the person to implement coping strategies focused on the management of objective damage, as well as on the search for emotional relief, a consideration that gives rise to the name of dual parallel processing in CS (DPP-CS). Brief intervention is understood as the involvement of motivational processes to enable the person to make decisions regarding emotional and instrumental coping which move her in the direction of emotional relief or solution of the crisis. The paper concludes with a summary of the three basic sources taken from the psychological literature to inform the design of the DPP-CS: the dual extended parallel process model, the cognitive theory of stress and coping, and the formulation by levels in cognitive therapy.